Effects of circuit-type resistance training on industrial opiate induced neurotransmitter disruption and performance changes of previously addicted men - Arazi Hamid; Dadvand Seyedeh Shiva (Sciendo, 2020)
Study aim: The aim of this study was to examine the effects of an 8-week circuit-type resistance training program on performance changes and neurotransmitter disruptions induced by industrial opiate in previously addicted men.